Stability of marsh edge berms constructed from fine-grained dredged sediment - Perkey, David W.; Tedesco, Lenore P.; Fall, Kelsey A.; Huff, Thomas P.; Chasten, Monica A. (Frontiers in Marine Science, 2024)
Due to observed impacts of sea level rise, many sediment management strategies in coastal settings are seeking ways to beneficially use locally dredged sediment in restoration, nourishment, and construction projects. The placement of sediment in shallow, near-marsh areas is a promising application of dredged material to both increase accretion and provide protection to marshes and intertidal flats in back bay areas. However, dredged material in these areas often include fine-grained (<63 m) sediments (FGS), that frequently raise questions concerning dispersion, stability, and environmental impact of the placement project. In 2020, approximately 30,500 m3 of FGS from the New Jersey Intracoastal Waterway (NJIWW) was placed along the southern edge of Gull Island, New Jersey to evaluate the feasibility of using FGS for beneficial use projects in near marsh environments. Gull Island was experiencing extensive marsh edge erosion through margin collapse. The placement was unconfined and resulted in the formation of two intertidal muddy berm-like features up to 0.7 m thick along more than 500 m of marsh. Bathymetric surveys showed that approximately 60-70% of the berm volume remained 36 months after placement, however maximum berm thickness reduced to 0.5 m. Field monitoring performed during construction found that turbidity plumes were localized to within 100 m of the placement site and sediment cores collected in June 2022 did not show systemic winnowing from the berm surface. Laboratory and field observations indicated that the berm material was cohesive in nature and produced large aggregates upon erosion, limiting the dispersal of FGS. Observations of current velocities and waves in the area indicate a low energy system such that the cohesive berm was largely resistant to erosion and that reduction in berm volume was largely due to consolidation and compaction. This suggests that shallow water features can be constructed with FGS in similar low energy environments with limited dispersal during and following construction, while being robust enough to help stabilize the marsh edge and improve marsh survivability against sea level rise.